2021
DOI: 10.3390/cancers13030410
|View full text |Cite
|
Sign up to set email alerts
|

Specific Inhibition of HIF Activity: Can Peptides Lead the Way?

Abstract: Reduced oxygen availability (hypoxia) is a characteristic of many disorders including cancer. Central components of the systemic and cellular response to hypoxia are the Hypoxia Inducible Factors (HIFs), a small family of heterodimeric transcription factors that directly or indirectly regulate the expression of hundreds of genes, the products of which mediate adaptive changes in processes that include metabolism, erythropoiesis, and angiogenesis. The overexpression of HIFs has been linked to the pathogenesis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 132 publications
(185 reference statements)
1
17
0
Order By: Relevance
“…Below, we briefly report the main aspects of the inhibition strategy and examples of chemical agents used. For a more detailed discussion about drugs, targets, and mechanisms, more specific reviews should be consulted [ 121 , 122 , 123 ].…”
Section: Targeting Hif-1 In Cancer Therapymentioning
confidence: 99%
“…Below, we briefly report the main aspects of the inhibition strategy and examples of chemical agents used. For a more detailed discussion about drugs, targets, and mechanisms, more specific reviews should be consulted [ 121 , 122 , 123 ].…”
Section: Targeting Hif-1 In Cancer Therapymentioning
confidence: 99%
“…Targeting transcription factors using small molecules is known to be difficult because of complicated protein–protein and/or protein-DNA interactions. Interestingly, recent progress in peptide-based drug targets has been shown to accomplish such challenges to some extent [ 54 , 55 ]. However, it should be noted that targeting a transcription factor that regulates many biological processes may simultaneously disrupt other critical physiological responses, and further research is needed before clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive investigation during the past decades has shown that HIF-1α and HIF-2α are significantly controlled by diverse intracellular signaling pathways not directly affected by oxygen levels. Most of these pathways culminate in HIF-1α/HIF-2α phosphorylation, which regulates their stability, localization, protein interactions, and subsequently activity ( Figure 4 ) [ 25 , 78 ].…”
Section: Vitamin D Crosstalk With Hif Signalingmentioning
confidence: 99%
“…As such, HIFs are often correlated with resistance to conventional therapy options and negative patient prognosis, much like vitamin D deficiency. Given the essential impact of HIFs and hypoxia in cancer, it is no wonder that HIFs are meaningful targets for agents with anticancer abilities, including naturally occurring compounds [ 24 , 25 , 26 ]. Furthermore, apart from HIF induction, lack of oxygen contributes to dysregulated signaling cascades [ 27 ] and compromised catalytic activity of enzymes such as the monooxygenase family members that use the molecular oxygen as a substrate and are heavily implicated in vitamin D converting reactions [ 28 ].…”
Section: Introductionmentioning
confidence: 99%